PENGARUH KECERDASAN EMOSIONAL DAN LITERASI DIGITAL TERHADAP KINERJA PEGAWAI GENERASI Z KOTA BIMA - Jaenab Jaenab; Novi Kadewi Sumbawati; Amirul Mukminin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
The purpose of this study was to determine the positive and significant influence of emotional intelligence and digital literacy on the performance of Generation Z employees in Bima City. This research is a quantitative study. This type of research is associative with the population used in this study, namely all Generation Z employees in Bima City. The sample used in this study was Generation Z employees in Bima City totaling 100 employees. The sampling technique in this study used purposive sampling based on criteria, the research instrument used was a questionnaire with a Likert scale. The analysis tool used in this study used multiple linear regression analysis using SPSS version 21. The results of this study are: 1) Emotional Intelligence does not have a positive and significant effect on the Performance of Generation Z Employees in Bima City. 2) Digital Literacy has a positive and significant effect on the Performance of Generation Z Employees in Bima City. 3) Emotional Intelligence and Digital Literacy have a positive and significant effect on the Performance of Generation Z Employees in Bima City.